Craniofacial proportions in children with adenoid or adenotonsillar hypertrophy are related to disease duration and nasopharyngeal obstruction. (May 2020) - Pawłowska-Seredyńska, Katarzyna; Umławska, Wioleta; Resler, Katarzyna; Morawska-Kochman, Monika; Pazdro-Zastawny, Katarzyna; Kręcicki, Tomasz
Highlights: Children with severe nasopharyngeal obstruction are diagnosed relatively early. Early diagnosis of adenotonsillar hypertrophy is crucial for normal facial development. Adenotonsillar hypertrophy at young age predispose to vertical facial growth.